Applied Statistics to Identification of the Causes of Delays Construction Project (Case Study of Construction Project in the Regency of Buton) - Muhammad Abdu; Muhammad Chaiddir Hajia; Sablyn Karsidi (PT Mattawang Mediatama Solution, 2022)
As the economy develops in Buton Regency, construction projects are increasing. However, not all projects in progress are going according to the targeted plan. For example, the construction of the Multipurpose Building in the Takawa Buton office complex which was built from 2016 until now has not been realized. Apart from that, there are also other projects such as the road connecting Gonda and Lapodi Village in Pasarwajo Subdistrict, the road connecting Siontapina and Sangiarano Villages in South Lasalimu Subdistrict, Kamaru Capital Road in Lasalimu Subdistrict, Bonetiro Village road in Kapontori Subdistrict, etc. are still pending. in the process. This type of research is a quantitative research, where the data is processed and tested with a statistical approach. Descriptive research that provides an overview of a situation where every problem and subject will be taught systematically, actually and accurately with a deductive discussion technique where the discussion starts from general things to more specific things. There are two methods used, namely validation test and reliability test. The solution to the factors that cause delays in construction projects in the Buton Regency area is that the unavailability of equipment can hinder the project's progress. The solution is not to rely on just one vendor. Make a list of vendors who can provide the necessary tools during the project. Make sure the vendors can provide everything on time